A number is written as 1 4 8 a in base a and 1 9 8 b in base b .
What is the number in base 10?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let the given number be N . It is given that
1 4 8 a a 2 + 4 a + 8 a 2 + 4 a a ( a + 4 ) = 1 9 8 b = b 2 + 9 b + 8 = b 2 + 9 b = b ( b + 9 )
Note that the right-hand side b ( b + 9 ) is always even (when b is even or odd). Therefore the left-hand side a ( a + 4 ) is always even too. But the left-hand side is only even when a is even. When a is even and a + 4 is also even, this means that the left-hand side is always divisible by 4 therefore the right-hand side b ( b + 9 ) is also always divisible by 4 . Since the number 1 9 8 b has 9 as a digit, b ≥ 1 0 . Then we have:
a ( a + 9 ) a 2 + 4 a − b ( b + 9 ) ⟹ a = b ( b + 9 ) = 0 = 4 + b ( b + 9 ) − 2 where 4 ∣ b ( b + 9 ) and b ≥ 1 0
The smallest b ≥ 1 0 , where 4 ∣ b ( b + 9 ) , is 1 1 . Then a = 2 2 4 − 2 not an integer. The next b is 1 2 ; and a = 2 5 6 − 2 = 1 4 . Then N = 1 4 2 + 4 ( 1 4 ) + 8 = 1 2 2 + 9 ( 1 2 ) + 8 = 2 6 0 .
Note: My method does not prove that the solution is unique.
148 in base a = 198 in base b
a² + 4a + 8 = b² + 9b + 8
a(a + 4) = b(b + 9)
Since RHS is a multiplication between an odd and an even number, a must be a positive even number. Also, since the difference between the numbers in RHS is 9, either both are multiple of 3 or both aren't. Supposing b isn't a multiple of 3, then neither a nor a+4 can be one, too. This would only be possible when their mean, (a + (a + 4)) / 2 = a + 2 is a multiple of 3 or a = 3x – 2 and a + 4 = 3x + 2 for a LHS of (3x – 2)(3x + 2)
= 9x² – 4
= one less than a multiple of 3.
Meanwhile, RHS would be (3y ± 1)(3z ± 1)
= 9yz ± 3(y + z) + 1
= one more than a multiple of 3
≠ the result in LHS
==> The supposed RHS with 2 non-multiples of 3 is impossible
[ Also can be done as (3y + 1)(3y + 10) and/or (3y – 1)(3y + 8) for a result of 9y² + 33y + 10 and 9y² + 21y – 8 respectively, which can be reduced to { 3(3y² + 11y + 3) + 1 } for the former and { 3(3y² + 7y – 3) + 1 } for the latter ].
Therefore, other than the fact that the even number between b and b+9 is a multiple of 4 (from the double evens of a and a+4 of LHS), b and b+9 of RHS also influenced the LHS in return by them being two multiples of 3 making one of a or a+4 to be a multiple of 3² = 9 (can't have the two in LHS to carry the factors of 3 separately since their difference is 4).
Then the least the LHS pair could be is 14 × 18 and the next should be 18 × 22. The first have a solution of 14 × 18 = 12 × 21 but none found for the second one (18 = 2 × 3² & 22 = 2 × 11, taking out the 3s we need the rest of 2, 2 and 11 to be divided into two groups in which their products differ by 3 but the smallest difference is 11 – 2² = 7 ≠ 3).
Now having a = 14 and b = 12, in base 10 the number equals
= 1 × 14² + 4 × 14¹ + 8 × 14⁰
= 196 + 56 + 8
= 260
Or = 1 × 12² + 9 × 12¹ + 8 × 12⁰
= 144 + 108 + 8
= 260
From given data, we can form 2 equations, a²+4a+8=b²+9b+8 => a+2= b ² + 9 b + 4 . And a>b>9 [since, 9 is representable in base b, b must be bigger than 9, and 148<198, thus a must be bigger than b]. But since b>9, b²+6b+9<b²+9b+4<b²+10b+25, but the middle term is bounded by 2 perfect squares and it must be a perfect square in itself, thus only possibility is b²+9b+4=b²+8b+16 => b=12. Putting b=12 in 1st equation we have a=14 and the original number base 10 to be 260
Problem Loading...
Note Loading...
Set Loading...
This involved some sneaky steps so I've tried to explain as much as possible as I go below - you could write this solution in a few lines but it might not be the easiest to understand! Let me know if anything's not clear.
Writing the numbers out in full, we have a 2 + 4 a + 8 = b 2 + 9 b + 8
We want to solve this in positive integers, with a > 8 and b > 9 . Since there's only one equation in two unknowns, we'll have to use properties of integers to solve it; we want to limit the number of possible solutions as much as possible. (This more or less rules out treating this as a quadratic, for example.)
This idea motivates the following manipulation: a 2 + 4 a + 8 a 2 + 4 a + 4 ( a + 2 ) 2 4 ( a + 2 ) 2 ( 2 a + 4 ) 2 ( 2 a + 4 ) 2 ( 2 b + 9 ) 2 − ( 2 a + 4 ) 2 = b 2 + 9 b + 8 = b 2 + 9 b + 4 = b 2 + 9 b + 4 = 4 b 2 + 3 6 b + 1 6 = ( 2 b + 9 ) 2 − 8 1 + 1 6 = ( 2 b + 9 ) 2 − 6 5 = 6 5 recognising a square on the left wanting a square on the right
So we have two integers, x = 2 b + 9 and y = 2 a + 4 , with a difference of squares equal to 6 5 ; ie ( x + y ) ( x − y ) = 6 5 .
This does the trick - 6 5 = 5 ⋅ 1 3 only factorises in a few ways, so we have the reduction to case analysis.
Further, note that since a and b are positive, and the two factors of 6 5 have to have the same sign, we must have x + y > x − y > 0 ; so there are only two cases to consider.
Case 1: x + y = 1 3 , x − y = 5
Solving these leads to x = 9 , y = 4 , from which we get a = 0 and b = 2 ; but this solution isn't valid as a is not positive.
Case 2: x + y = 6 5 , x − y = 1
Solving these leads to x = 3 3 , y = 3 2 , from which we get a = 1 4 and b = 1 2 , which works. To check, we get 1 4 2 + 4 × 1 4 + 8 = 1 2 2 + 9 × 1 2 + 8 = 2 6 0 which is the required answer.